2005
DOI: 10.2106/jbjs.d.01921
|View full text |Cite
|
Sign up to set email alerts
|

Open Operative Treatment for Anterior Shoulder Instability

Abstract: The treatment of anterior glenohumeral instability continues to evolve. Open capsulolabral repairs are time-tested and reliable. In an era in which arthroscopic techniques continue to improve, open surgery remains an acceptable option, and there are still certain injury patterns that cannot be adequately addressed arthroscopically. Decision-making regarding surgery for instability is influenced by the surgeon's experience and the relevant pathological findings. Open operative treatment is the preferred approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 123 publications
(171 reference statements)
0
85
0
9
Order By: Relevance
“…Warner et al reported a good outcome after using hamstring tendons. Gallie and Le Mesurier described the use of iliotibial band with irreparable capsule, and the results were generally good, with no recurrences [13] [14]. This patient also had greater tuberosity fracture, but it was successfully reduced and fixed by TBW technique [15].…”
Section: Discussionmentioning
confidence: 84%
“…Warner et al reported a good outcome after using hamstring tendons. Gallie and Le Mesurier described the use of iliotibial band with irreparable capsule, and the results were generally good, with no recurrences [13] [14]. This patient also had greater tuberosity fracture, but it was successfully reduced and fixed by TBW technique [15].…”
Section: Discussionmentioning
confidence: 84%
“…Das liegt daran, dass keine einheitliche bildgebende Diagnostik verwendet wird und die Interpretation und Klassifikation der knöchernen Läsionen unterschiedlich gehandhabt werden [4,9,22]. Bei genauerer Analyse finden sich initial nach traumatischer vorderer Erstluxation knöcherne Glenoidrandabrissfrakturen ("Bankart-Fraktur") in 20-30% der Fälle [9].…”
Section: Vorbemerkungenunclassified
“…Die akute knöcherne Bankart-Läsion mit Dislokation des Pfannenrandfragments (Abriss des LabrumLigament-Kapsel-Komplexes mit knöchernem anteroinferiorem Glenoidrand) stellt wegen der Gefahr der Reluxation und der sekundären Progredienz anteroinferiorer Glenoiddefekte, die zum späteren Zeitpunkt nur durch nichtanatomische knöcherne Verfahren (Korakoidtransposition, autogene Spanplastik) [1,4,7,14,[22][23][24]40] beherrschbar sind, eine absolute Operationsindikation dar. Die Frage des offenen oder arthroskopischen Zugehens hängt von der Erfahrung und dem sicheren Umgang mit der arthroskopischen Technik ab [8,22,25,28,39].…”
Section: Abbildungunclassified
See 2 more Smart Citations